2012
DOI: 10.1021/jm201465w
|View full text |Cite
|
Sign up to set email alerts
|

Fluorocyclines. 1. 7-Fluoro-9-pyrrolidinoacetamido-6-demethyl-6-deoxytetracycline: A Potent, Broad Spectrum Antibacterial Agent

Abstract: This and the accompanying report (DOI: 10.1021/jm201467r ) describe the design, synthesis, and evaluation of a new generation of tetracycline antibacterial agents, 7-fluoro-9-substituted-6-demethyl-6-deoxytetracyclines ("fluorocyclines"), accessible through a recently developed total synthesis approach. These fluorocyclines possess potent antibacterial activities against multidrug resistant (MDR) Gram-positive and Gram-negative pathogens. One of the fluorocyclines, 7-fluoro-9-pyrrolidinoacetamido-6-demethyl-6-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
98
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 109 publications
(99 citation statements)
references
References 45 publications
1
98
0
Order By: Relevance
“…For in vitro susceptibility testing, commercial-grade antibiotics were obtained from the USP (Rockville, MD), ChemPacific Corp. (Baltimore, MD), or SigmaAldrich (St. Louis, MO), and TP-271 was synthesized at Tetraphase Pharmaceuticals as described previously by Xiao et al (23). Antibiotics for susceptibility testing were prepared in sterile deionized water and stored frozen at ՅϪ65°C.…”
Section: Methodsmentioning
confidence: 99%
“…For in vitro susceptibility testing, commercial-grade antibiotics were obtained from the USP (Rockville, MD), ChemPacific Corp. (Baltimore, MD), or SigmaAldrich (St. Louis, MO), and TP-271 was synthesized at Tetraphase Pharmaceuticals as described previously by Xiao et al (23). Antibiotics for susceptibility testing were prepared in sterile deionized water and stored frozen at ՅϪ65°C.…”
Section: Methodsmentioning
confidence: 99%
“…Eravacycline (formerly TP-434) is a novel, fully synthetic antibiotic of the tetracycline class (8). Eravacycline was designed to be active against the two main acquired tetracycline-specific resistance mechanisms, ribosomal protection and active drug efflux (9,10).…”
mentioning
confidence: 99%
“…In in vitro studies, the compound has shown potent activity against a broad spectrum of susceptible and multidrug-resistant bacteria, including Gram-negative, Gram-positive, and anaerobic bacteria (11). Eravacycline has a potency profile similar to that of carbapenems except that it more broadly covers Gram-positive pathogens, like methicillin-resistant Staphylococcus aureus and enterococci, is active against carbapenem-resistant Gram-negative bacteria, but is not active against Pseudomonas aeruginosa (8).…”
mentioning
confidence: 99%
“…Antibiotics and media. Eravacycline was synthesized at Tetraphase Pharmaceuticals as described in Xiao et al (11). Tigecycline for injection (Pfizer, Groton, CT) was purchased from Skenderian Apothecary, Cambridge, MA.…”
mentioning
confidence: 99%